(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
Pharmaceutical services correspond to a set of actions that aim to guarantee the integral access and rational use of drugs by the population. In this sense, this study aimed to identify the frequency and conditioning factors for clinical services of primary care in the Federal District, Brazil. A quantitative cross-sectional study was conducted, in which 34 pharmacists were interviewed. The most frequently developed clinical pharmaceutical services were dispensing, pharmaceutical guidance for users, and technical-pedagogical activities for the health team. There is a greater frequency of operation of clinical services by pharmacists working in pharmacies with physical infrastructure, with better levels of adequacy, greater support from management and health staff, and the inclusion in Family Health Support Nucleus activities. Although the clinical pharmaceutical services in primary care are incipient, the study raises important data for the reorientation and qualification of these actions.